Extração de compostos bioativos a partir de resíduo de molho de soja com dióxido de carbono em condições supercríticas - Oliveira, Mayra Thomás (2023)
Soy sauce is the most popular liquid condiment around the world. Between 10 and 20% of the shoyu mass produced becomes waste rich in oil, fibers, proteins, isoflavones, cellulose and amino acids. Use this waste to obtain by-products becomes quite attractive, because it adds value to a material usually discarded in the environment or used as animals feed. That way, this work aimed to study of supercritical extraction of shoyu mash residue. The effects of pressure (200 and 250 bar), temperature (40 and 60 °C) and addition of cosolvents (ethanol and hexane) on the yield and composition of extracts were valuated. A kinetic behavior analysis of supercritical extraction was made through the global extraction curves and models reported in the literature (logistic and spline). Soxhlet method was applied using ethanol, acetone and hexane as cosolvents for comparison purposes. The yields obtained by supercritical extractions varied between 15.93 and 20.51%. The pressures influenced in these results, as opposed to the addition of cosolvent and temperature variation. Spline model presented a good fit for all the global extraction curves, unlike the logistic model. In Soxhlet extraction, the yield ranged from 25.16 to 31.03%, and ethanol was the solvent with the best performance. The residue, which was submitted to a salt removal process, presented significant amounts of fibers (38.20 g/g processed residue), carbohydrates (37.31 g/g processed residue) and proteins (13.90 g/g processed residue), and can be used for food supplementation. The extracts obtained showed linolenic acid in major quantity, followed by oleic acid, palmitic acid and linolenic acid. The extracts also showed slightly active antioxidant activity, phenolic compounds between 176.43 and 60.5 mg rutin/100 g dry processed residue and flavonoids between 82.42 and 7.05 mg salic acid equivalent/100 g dry processed residue. Thus, optimizing the use of soy sauce residue would generate by-products, reduce costs with its treatment, environmental problems and turn the production of shoyu more sustainable.